(untitled) (Research, Society and Development, 2022)
Introduction: Hair has a vast importance in appearance and self-esteem, telogen effluvium increases hair loss, from 100 to 400 hairs/day, and may be associated with COVID-19, because of medications, emotional stress and alteration of the hair cycle because of the SARS-CoV-2 virus. Objective: Literature review on the relationship of telogen effluvium post COVID-19. As well as associating the relationship of symptoms, it has the relationship with hair loss. Method: For the development of the following integrative review, the following databases were used: VHL, PubMed. The inclusion criteria were: articles with full text available for reading, published in English, Portuguese or Spanish. Result: The articles found had several opinions not finding the exact cause of which the virus induces hair loss, which may be related to the medication, emotional stress, symptoms of the disease itself such as high fever. Even the virus not distinguishing sex is more reported in women. Conclusion: Since the exact cause of telogen effluvium after COVID-19 is not known, there is no specific treatment for the cases and should follow the same guidelines already existing for telogen effluvium in dermatology.